An improved piezoelectric ceramic transducer for ultrasonic applications in air - BINDAL, V. N.; CHANDRA, Mukesh (Archives of Acoustics, 1982)
The design considerations of a new type of piezoelectric ceramic transducerfor transmitting and receiving ultrasonic waves in air have been reported. This transducer contains a bilaminar assembly consisting of a piezoelectric ceramic disc and a metallic plate which oscillates in flexural mode. This bilaminar assembly mounted at its nodal circle can be designed to operate at a fixed frequency in the range of 25 to 50 kHz.The constructional details and the working of the transducer have alsobeen given. The resonant frequencies f_exp observed experimentally for transducers having good transmitting and receiving sensitivities are found to be in good agreement with the values f_cal derived from theoretical considerations. This closed-type transducer is rugged and compact and can be employed with advantage in several indoor as well as outdoor uses in automation, sensing and remote control applications.